Adherence to lifestyle modification in patients with nonalcoholic fatty liver disease - K. A. Andreev; Yu. P. Skirdenko; N. A. Nikolaev; M. A. Livzan; A. V. Gorbenko; M. M. Fedorin; T. S. Krolevets (Бюллетень сибирской медицины, 2022)
Nonalcoholic fatty liver disease (NAFLD) makes a major impact on morbidity and mortality among the workingage population in developed countries. In the lack of effective pharmacological methods, the leading role in treatment of NAFLD belongs to lifestyle modification, consistent and gradual weight loss, and its maintenance. The qualitative and quantitative structure of the diet, intensity of physical activity, and most importantly, regularity and consistency of implementation of lifestyle modification activities are the key to successful management of patients with NAFLD.To date, there are very few studies on adherence to lifestyle modification activities in this group of patients, which is mainly due to a deficiency of methodological tools. The questionnaire “QAA-25” recommended by the Russian Scientific Medical Society of Therapists for quantitative assessment of adherence to treatment allows to assess both adherence to therapy in general and adherence to its individual components (adherence to drug therapy, adherence to medical counseling, and adherence to lifestyle modification), which requires further study taking into account features of therapeutic strategies in treating NAFLD.